Imperial Borderland? Fear and Rivalry in Representations in Print of the Landscape of Carolina and Louisiana 1660-1753 - Catherine ARMSTRONG (E-REA)
For the first half-century of settlement by Europeans, the colonies of Carolina and Louisiana were imperial borderlands. Looking west, Carolinians were among the first settlers to highlight and experience the threat that the French posed once they had traversed and mapped the length of the Mississippi. Although during this period the efforts to claim, survey and document landownership were flourishing, the reality of struggling to clear and use tracts of many hundreds of acres meant that much of the region remained ‘wilderness’ despite being nominally owned by Europeans.This paper compares British and French printed accounts that symbolically brought this land under control. I argue that European efforts to bring the landscape, flora and fauna of the southeast under control were problematic even in areas not previously understood as ‘borderlands’, such as parts of Charles Town and New Orleans themselves. While the accounts do reflect a feeling of increasing imperial confidence on the part of the British and the French, during this period neither was able to fully control the landscape they professed to have mastered. This paper shows that it was the vulnerability, not the strength, of these powers that struck the authors whose work is surveyed here.